2015
DOI: 10.12968/bjhc.2015.21.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Infusion device standardisation and dose error reduction software

Abstract: In 2004, the National Patient Safety Agency (NSPA) released a safety alert relating to the management and use of infusion devices in England and Wales. The alert called for the standardisation of infusion devices and a consideration of using centralised equipment systems to manage device storage. There has also been growing interest in smart pump technology, such as dose error reduction software (DERS) as a way to reduce IV medication errors. However, questions remain about the progress that has been made towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Although such pumps have been widely implemented in the USA, take-up in England has been patchy and, even where smart pumps have been introduced, drug libraries may be only partially implemented. 5 There have been few studies of the role of infusion devices in ensuring safe medication administration practices, and most previous studies have taken place in the USA. 6,7 The overall aim of the study, referred to as ECLIPSE (Exploring the Current Landscape of Intravenous Infusion Practices and Errors), was to better understand current intravenous (IV) infusion practices in England and the possible role of smart pumps in managing patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such pumps have been widely implemented in the USA, take-up in England has been patchy and, even where smart pumps have been introduced, drug libraries may be only partially implemented. 5 There have been few studies of the role of infusion devices in ensuring safe medication administration practices, and most previous studies have taken place in the USA. 6,7 The overall aim of the study, referred to as ECLIPSE (Exploring the Current Landscape of Intravenous Infusion Practices and Errors), was to better understand current intravenous (IV) infusion practices in England and the possible role of smart pumps in managing patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Although smart pumps were in use in 68% of US hospitals in 2011, 19 a figure now likely to be much higher, their use is not yet as widespread in the UK. 5 Such technology can potentially identify and prevent some kinds of medication errors, but cannot prevent all possible errors. Smart pump use also comes at a cost, both financially and in terms of the changes needed to make their use effective.…”
Section: The Potential Role Of Smart Infusion Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples given of the benefits of introducing a library are cost reductions, standardization, safer storage, improved access for maintenance and help in facilitating training. Recent surveys have shown that adoption of centralized libraries has not increased markedly since 1999, with between 7-34% uptake, depending on clinical specialty [4].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation rates in European hospitals fall far below those in the United States, where for the last decade accreditation has been linked to implementation 1 2. Multidisciplinary collaboration is essential, with pharmacy input and the creation of a smart pump drug library recognised as often being limiting, yet crucial factors, to implementation 3.…”
mentioning
confidence: 99%